Propofol, but not etomidate, increases corticosterone levels and induces long-term alteration in hippocampal synaptic activity in neonatal rats - Xu, Changqing (Neurosci Lett, 2016)
Animal studies provide strong evidence that general anesthetics (GAs), administered during the early postnatal period, induce long-term cognitive and neurological abnormalities. Because the brain growth spurt in rodents is delayed compared to that in humans, a fundamental question is whether the postnatal human brain is similarly vulnerable. Sevoflurane and propofol, GAs that share positive modulation of the gamma-aminobutyric acid type A receptor (GABA(A)R) function cause marked increase in corticosterone levels and induce long-term developmental alterations in synaptic activity in rodents. If synaptogenesis is affected, investigation of mechanisms of the synaptic effects of GAs is of high interest because synaptogenesis in humans continues for several years after birth. Here, we compared long-term synaptic effects of etomidate with those of propofol. Etomidate and propofol both positively modulate GABA(A)R activity, but in contrast to propofol, etomidate inhibits the adrenal synthesis of corticosterone. Postnatal day (P) 4, 5, or 6 rats received five injections of etomidate, propofol, or vehicle control during 5 h of maternal separation. Endocrine effects of the anesthetics were evaluated by measuring serum levels of corticosterone immediately after anesthesia or maternal separation. The frequency and amplitude of miniature inhibitory postsynaptic currents (mIPSCs) in hippocampal CA1 pyramidal neurons were measured at P24-40 and P≥80. Only propofol caused a significant increase in serum corticosterone levels (F((4,26)) = 17.739, P < 0.001). In contrast to increased frequency of mIPSCs in the propofol group (F((4,23)) = 8.731, p < 0.001), mIPSC activity in the etomidate group was not different from that in the vehicle groups. The results of this study together with previously published data suggest that anesthetic-caused increase in corticosterone levels is required for GABAergic GAs to induce synaptic effects in the form of a long-term increase in the frequency of hippocampal mIPSCs.